The Effect of Business Location on the Income of Fruit Traders in Baolan District, Tolitoli Regency - Ramlawati; Hilmi; Abdul Rajab (Dwijendra University, 2022)
This study aims to determine the effect of business location on the income of fruit traders in Baolan District, Tolioli Regency. The method used is a quantitative method with data collection techniques through questionnaires. The sample taken amounted to 30 respondents. The analysis tool uses SPSS for windows 26. Which includes validity test, reliability test, simple linear regression and product moment correlation. Based on the results of research and discussion, it is concluded that the correlation value is 0.601. This indicates that there is a unidirectional relationship between business location and income. And it can be stated that the correlation between variable X (Business Location) and Variable Y (Revenue) is strong and positive. the coefficient of determination is: r² = 0.36. This shows that the effect of business location on the income of fruit traders in Baolan District, Tolitoli Regency is 36%. The steps that should be taken by traders are: traders should be able to further increase the selection of more strategic locations with the aim of increasing income.